(untitled) (Bangladesh Journal of Zoology, 2013)
A study was conducted about vulnerable shark and ray species availability and their percentage composition in two fish landing centers at Fishery ghat, Chittagong and BFDC fish harbor, Coxs Bazar district during April 2006 through March 2012. A total of 35 species (11 shark and 24 ray species) was identified within these six years. Out of 35 species, only one vulnerable shark species, the silky shark Carcharhinus falciformis (Muller and Henle, 1839), was not abundant all the year round and three were vulnerable ray species, Javanese cow ray Rhinoptera javanica (Muller and Henle, 1841), banded eagle ray Aetomylaeus nichofii (Bloch and Schneider, 1801) and white spotted shovelnose ray Rhynchobatus laevis (Bloch and Schneider 1801) were found throughout the year during the study period. The average percentage composition by weight of C. falciformis was 1.38 and the availability of average number was 3202. The average percentage contribution and the landed average number of vulnerable R. javanica, A. nichofii and R. laevis species were 1.46% (948 numbers), 0.61% (554 numbers) and 0.54% (298 numbers), respectively of the total catch. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14316 Bangladesh J. Zool. 40(2): 221-229, 2012